2010
DOI: 10.1007/s11244-010-9499-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure Effects of Potassium-Based TiO2 Sorbents on the CO2 Capture Capacity

Abstract: The CO 2 absorption properties of potassiumbased TiO 2 sorbents prepared by calcining at various temperatures from 300 to 700°C under N 2 and air were investigated in a fixed bed reactor at 60°C. The CO 2 capture capacity of the sorbent was changed dramatically depending on the structure of the sorbent, which was affected by calcination atmosphere, as well as calcination temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…For K 2 CO 3 /AC, K 2 CO 3 /TiO 2 , and K 2 CO 3 /ZrO 2 , the CO 2 desorption peak was consistent with the production of KHCO 3 as the only product for these sorbents (Lee et al, 2009;Lee & Kim, 2007). The calcination temperature of K 2 CO 3 /TiO 2 must be lower than 300 C (Lee et al, 2010) because it was found that its carbonation reaction capacity rapidly decreased when the calcination temperature increased from 300 to 700 C, and some byproducts such as K 2 Ti 2 O 5 , K 2 Ti 6 O 13 , and K 2 Ti 4 O 9 were also formed from K 2 CO 3 and TiO 2 . The TPD results for K 2 CO 3 /MgO (Lee, Chae, et al, 2008;Lee & Kim, 2007;Xiao et al, 2011) show three CO 2 peaks, one occurs at 130 C (as expected for KHCO 3 production), another occurs at around 300 C (which suggests the presence of Mg(OH) 2 ), and the last is seen at a temperature above 340 C (attributed to K 2 Mg(CO 3 ) 2 and K 2 Mg(CO 3 ) 2 $4(H 2 O)).…”
Section: Sorbent Regeneration Characteristicssupporting
confidence: 52%
See 4 more Smart Citations
“…For K 2 CO 3 /AC, K 2 CO 3 /TiO 2 , and K 2 CO 3 /ZrO 2 , the CO 2 desorption peak was consistent with the production of KHCO 3 as the only product for these sorbents (Lee et al, 2009;Lee & Kim, 2007). The calcination temperature of K 2 CO 3 /TiO 2 must be lower than 300 C (Lee et al, 2010) because it was found that its carbonation reaction capacity rapidly decreased when the calcination temperature increased from 300 to 700 C, and some byproducts such as K 2 Ti 2 O 5 , K 2 Ti 6 O 13 , and K 2 Ti 4 O 9 were also formed from K 2 CO 3 and TiO 2 . The TPD results for K 2 CO 3 /MgO (Lee, Chae, et al, 2008;Lee & Kim, 2007;Xiao et al, 2011) show three CO 2 peaks, one occurs at 130 C (as expected for KHCO 3 production), another occurs at around 300 C (which suggests the presence of Mg(OH) 2 ), and the last is seen at a temperature above 340 C (attributed to K 2 Mg(CO 3 ) 2 and K 2 Mg(CO 3 ) 2 $4(H 2 O)).…”
Section: Sorbent Regeneration Characteristicssupporting
confidence: 52%
“…The energy consumption for the CO 2 recovery was evaluated in multiple tests on CO 2 sorption and release. Further research on CO 2 capture using dry potassium-based sorbents was conducted by Kyungpook National University (Lee, Chae, et al, 2008;Lee et al, 2009Lee et al, , 2010Lee & Kim, 2007), KEPRI (Lee, Eom, et al, 2011), and the Korea Institute of Energy Research (KIER) Seo et al, 2005Seo et al, , 2009. Kyungpook National University has been attempting to develop various sorbent formulations as well as to carry out the basic research.…”
Section: Basic Technology Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations